Management of communication 2.0 in public health campaigns in the Andean Community - Chamba-Maza, Cecibel del Cisne (2021)
The study offers an analysis of the process of Communication 2.0 in the social accounts of the health authorities belonging to the Andean Community during the worldwide public health campaigns. Qualitative and quantitative methods were brought together in order to measure content analysis and user involvement. Interviews with experts supplement the findings. Results: None of the health organizations generated an optimal Communication 2.0 index, on FaceBook, corporate messages predominated, but they were not interactive. On Twitter, the messages were educational but not corporate. The health bodies which were evaluated are essential organs of formal communication, so their communication strategies should be focused on the needs of their audience. A weak Communication 2.0 and a weak level of interest have been noted in the mandated campaign of these essential bodies that encompass, in considerable measure, institutional management. Nevertheless, users show a greater engagement with educational programs, principally computer graphics and videos, on Facebook.